PERANAN KEPALA DESA DALAM PELAKSANAAN BADAN USAHA MILIK DESA (BUMDES) DI DESA LABBO KECAMATAN TOMPOBULU KABUPATEN BANTAENG - Rabina Yunus (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2015)
This study aims at knowing the role of the head of village and the factors which influence the implementation of village-owned enterprises in Labbo Village Tompobulu Subdistrict Bantaeng Regency. The type of study was descriptive research. Data was collected by using observation, interview, library and documentation techniques. The data collection was obtained in some sources and the informant was determined by selecting informant who has a role and technically involved in the implementation of village-owned enterprises. The data was analyzed qualitatively and explained to draw a conclusion. This study explains that the head of village who held as ex-officio commissioner (run two position in one system) has very good roles in the implementation of village-owned enterprises in Labbo village especially in the planning, organizing, implementing and controlling. The influential factors in the management of village-owned enterprises in Labbo village are consisting of supporting and inhibiting factors. The supporting factor includes the potential of resources such as natural resources and human resources, grant from the local government, operational facilities of village-owned enterprises. Then, the inhibiting factor includes the lack of proper policies by the head of village, socio-political condition in Labbo village, the lack of coordination between commissioner and director. Keywords: the role of the village head, the management BUMDes